An Examination on the Perception Towards Censorship on Library Services Delivery among Staff of Kwara State University Library - Abdulfatai, Saliu (PT Mattawang Mediatama Solution, 2024)
The study was conducted on the perception towards censorship on library services delivery among staff of Kwara State University library. the study formulated used five research questions and used total enumeration sampling techniques because the population is too small (24) the entire population. A survey method was used in undertaking the study, in which answers were sought on the perception of librarians towards censorship and intellectual freedom, the strategies Kwara state University library adopted to prevent the problem or occurrence of censorship, the extent at which academic librarians in Kwara state promotes intellectual freedom, the types of censorship available in the collection of Kwara state university library, the types of censorship that can affect both library and it collection. Questionnaire was the main instrument used for data collection. The instrument was subjected to validation by the supervisor and expert in measurement and evaluation and the data collected from the study were analyzed using (SPSS), frequency tables and percentage. The study discovered that there are different types of censorship available in the collection of Kwara state university library; and types of censorship that can affect both library and it collection; These include Prior censorship, Post censorship, Corporate Censorship, Religious Censorship, Political Censorship, Military Censorship, and Moral Censorship. In conclusion the study made some recommendations which include that: educating users (students and staffs) about intellectual freedom, advocacy to the government, maintaining confidentiality of library record as strategies Kwara state University library adopted to prevent the problem or occurrence of censorship.